How can L´Oréal Paris (makeup) be an attractive brand for millennials in Portugal? - Monteiro, Rita Costa Pinheiro Alves (2020)
As an intern at L’Oréal Paris (Makeup) in Portugal, I developed this work project based on the main challenge that the brand is now facing: How can L’Oréal Paris (makeup) better engage the new millennial generation?”. Firstly it was conducted a primary and secondary research. Based on the research, we recommended L’Oréal Paris to (a) follow a brand strategy which understands millennials and therefore fulfill their needs and expectations regarding makeup and (b) change its distribution strategy in order to improve brand image and to gain market prominence.